Nurturing Ubuntu, the African Form of Human Flourishing Through Inclusive Home Based Early Childhood Education - Ejuu, Godfrey; Opiyo, Rose Atieno (Frontiers in Education, 2022)
Human flourishing has recently gained more attention in the world as a prerequisite safety net for better human resilience in uncertain times. While most Western authors believe that human flourishing is an individual issue, gained in later life, African communities that are largely communal may not have the same view. Communalism as opposed to individualism as a key pillar in African Ubuntu thinking makes it a possibility that there is a departure in the contextualisation of human flourishing and its pathways. This explores the African conceptualisation of flourishing in the Ubuntu lens and how communities are coming together to cultivate it by implementing home based early childhood learning centres. Desk review was used to learn the contextual meaning of human flourishing and different pathways to it in African community settings. Home based early learning centres operated by parents was seen as a core activity to nurture Ubuntu, as each family and community member becomes useful in provide a service that helps others to flourish at different stages of life. The paper concludes that the use of the home-based early childhood model as a flourishing intervention helps to engage every member of the community for the good of their children, bringing live the Ubuntu saying ‘I am a person because of other persons’. This study is significant in that it proposes home-based early learning as a more viable pathway way to human flourishing and redirects the focus of flourishing to a younger age group.